Mechanisms of increased pain discrimination by contingent reinforcement: a perceptual decision-making and instrumental learning account - Hubschmid, Fabrice; Flury, Melissa Luna; Löffler, Martin; Desch, Simon; Becker, Susanne (Pain, 2025)
Recent evidence highlights that monetary rewards can increase the precision at which healthy human volunteers can detect small changes in the intensity of thermal noxious stimuli, contradicting the idea that rewards exert a broad inhibiting influence on pain perception. This effect was stronger with contingent rewards compared with noncontingent rewards, suggesting a successful learning process. In the present study, we implemented a model comparison approach that aimed to improve our understanding of the mechanisms that underlie thermal noxious discrimination in humans. In a between-subject design, 54 healthy human volunteers took part in a pain discrimination task with monetary rewards either contingent or noncontingent on successful discrimination of small changes in the intensity painful heat stimulation. We used models from 2 traditions in decision-making research, perceptual decision-making, and instrumental learning. Replicating the previous findings, only rewards contingent on behavior enhanced pain discrimination. Drift diffusion modelling revealed increased sensory signal strength and decreased response caution and nondecision times as mechanisms underlying this effect of contingent rewards on pain discrimination. In addition, reinforcement learning models indicated a temporal evolution of discriminative abilities reflected by a trial-by-trial increase of perceived signal strength only with contingent rewards but not with noncontingent rewards. Modelling of separate learning rates for positive and negative prediction errors indicated that this temporal evolution of discriminative abilities was driven by positive reward prediction errors. These results might indicate increased sensitivity towards better-than-expected outcomes in the temporal adaptation of pain discrimination abilities to a rewarding context in humans.